Predictive models for IOPs measured with NCT, GAT, and ORA among patients undergoing SMILE - Han, Tian; Shi, Wanru; Chen, Yingjun; Shen, Yang; Xu, Ye; Zhou, Xingtao (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To develop predictive models for the intraocular pressure (IOP) of patients undergoing small incision lenticule extraction (SMILE) procedures, measured with a noncontact tonometer (NCT), Goldmann applanation tonometry (GAT), and an ocular response analyzer (ORA). Methods: In this prospective study, a total of 104 eyes (−6.23 ± 2.06 diopters) of 52 patients (24.38 ± 4.76 years) undergoing SMILE procedures were included. The intraocular pressure was measured (IOPNCT with NCT, IOPGAT with GAT, and IOPcc and IOPg with ORA) before surgery and at postoperative 6 months. Information on age, preoperative and attempted spherical equivalent (SE), ablation depth, preoperative values and postoperative changes in central corneal thickness (CCT), K1, K2, Km, corneal hysteresis (CH) and corneal resistance factor (CRF) values was collected in order to predict IOPs. Results: All surgeries were uneventful. At postoperative 6 months, the efficacy and safety index were 1.04 ± 0.15 and 1.08 ± 0.18, respectively. Significant decreases were detected in postoperative IOPNCT, IOPGAT, IOPcc, and IOPg compared to preoperative values (all p < 0.001). No relationship was found between any IOP and ablation depth, attempted SE, and preoperative SE, as well as CCTdifference (all p > 0.05). Predictive models for IOPs were constructed to predict preoperative values, and R2 values were 67.5% (IOPNCT), 64.5% (IOPGAT), 78.7% (IOPcc), and 82.0% (IOPg). The prediction band of IOPNCT and IOPGAT was 7.4–15.1 mmHg and 8–16 mmHg, respectively. Conclusion: Predictive models for IOP measurements after SMILE procedures can be helpful in clinical practice.